In silico evaluation of the efficacies of two different medicaments against Enterococcus faecalis - I B Geeta; A S Anjum Husna; S Sachin Sha; Ameen M Muhammed; J Moses (Wolters Kluwer Medknow Publications, 2019)
Aim: The aim of the study is to evaluate the efficacies of two different medicaments, such as ledermix and licorice pastes, against Enterococcus faecalis using in silico method. Methodology: Procurement of medicaments is from pharmaceutical shop. Culturing of E. faecalis is done under sterile conditions using brain-heart infusion broth. Bacterial growth check is done at 600 nm for further processing. Medicaments are mixed in double distilled for the analyses. After autoclaving at 121°C, the butylated hydroxyanisole is poured into Petri dishes to solidify. After solidification, wells are punched using sterile punchers. The punched plates are ultraviolet treated for 10 min before inoculating with the organism. About 100 mL of culture sample is inoculated and made a fine spread inside the Petri dish. The prepared medicaments are poured and incubated at 37°C for analysis. After incubation, the clear zone is measured mechanically for antimicrobial effect at the duration of 24 h and 3, 5, and 7 days for virulence factor. The growth of the bacteria is subjected to microscopic analysis. Molecular docking studies are to be carried out using in silico method to find out the action of medicaments against E. faecalis at the molecular level. Groups are Group I: ledermix paste and Group II: licorice paste + Ca(OH)2 at 1:1 ratio. Results: The zone of inhibition of licorice paste + Ca(OH)2 was higher at 24 and 48 h, whereas ledermix showed less significant zone of inhibition against E. faecalis. Conclusion: Combination of licorice + Ca(OH)2 completely inhibited the growth of E. faecalis. Licorice + Ca(OH)2 compounds show best results both in Microbial inhibition concentration (MIC) (6 ± 1 cm) and in docking mechanism (−7 K cal/mol). Comparatively, ledermix showed only (4 ± 1 cm) in Microbial inhibition concentration and only (−6.8 K cal/mol) in docking mechanism.